Integrating Puzzles and STAD Model in Teaching Angle Measurement to Elementary School Third Graders: An Action Research Study - Hery Setiyawan; Herfa Maulina Dewi Soewardini (Universitas Nahdatul Ulama Surabaya, 2023)
The purpose of this study was to improve the process (student activity and response) and learning outcomes of mathematics in the application of the STAD type cooperative learning model with puzzle media on the material for measuring angles for grade 3 students. Puzzle learning media applied in grade 3 about angles included sorting large sizes. angles, recognize and make the types of angles. This study uses classroom action research through at least two cycles to determine the improvement. If there is no improvement, then proceed to the third cycle and so on, until there is an increase. For data analysis using the percentage of classical completeness of the average percentage of observations. The results showed that the percentage of classical student activity in the first cycle was 63.13% with moderate success and 85.27% in the second cycle classical student activity with high success. The results of student responses using interviews in cycle I and cycle II both received 9 positive comments and 1 negative comment. This is a lot of students who give positive comments so that the response is said to be good. Meanwhile, the learning outcomes test in the first cycle with the classical percentage of 57.1% and in the second cycle as many as 29 students who completed the classical percentage 82.8% with an increase of 25.7% from the previous cycle. The conclusion that can be drawn from the research results is an increase in the percentage of student activity, student responses and learning outcomes.